Interaction Between Toxic and Essential Metals in The Biological System, and Their Effect on Animal Health - Darmono . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Among the various toxic elements, heavy metals such as Cd, Pb, and Hg are commonly present in the environment. These metals have  no  biological  function  in  the  animal,  but  their presence  in  tissues  reflect  contact  of  the  organism  with  its environment. Studies of the toxicity mechanism of these elements in the biological systems of the animals are important especially interaction between them and some essential dietari elements like Ca, Zn, Fe, Se, and Cu. In general a deficiency from one of the essential element increases toxicity of heavy metals, whereas an excess appears to be protective. These suggest that dietary presence of the essential elements may to protection of animal from the effects of heavy metal exposure. Addition of essential elements in the diet can be used for the treatment of heavy metal toxicity.   Key words : Toxic metals, essential metals, interaction